Medical specialists’ basic psychological needs, and motivation for work and lifelong learning: a two-step factor score path analysis - van der Burgt, Stéphanie M. E. (BMC Med Educ, 2019)
BACKGROUND: Continuing professional development and lifelong learning are crucial to secure safe and good quality healthcare. Lack of motivation has been found to be among the most important barriers for participation in lifelong learning. This study was conducted to investigate the relationships between medical specialists’ work motivation, lifelong learning motivation, autonomy, competence and relatedness satisfaction. METHODS: Self-Determination Theory was used as a theoretical framework for this study. Data were collected through an online survey, that was sent to all (N = 1591) medical specialists in four Dutch hospitals. The survey measured background characteristics, autonomy, competence, and relatedness satisfaction, autonomous and controlled work motivation, and lifelong learning motivation. Two step factor path analysis with the method of Croon was used to analyze the data from 193 cases. RESULTS: Autonomy need satisfaction was positively associated with autonomous work motivation which in turn was positively associated with lifelong learning motivation. Competence need satisfaction and age were negatively associated with controlled work motivation. Competence need satisfaction was also positively related with lifelong learning motivation. No significant nor any hypothesized associations were found for relatedness. CONCLUSIONS: Our findings, in line with Self-determination Theory literature, show that autonomy and competence need satisfaction are the important factors as they were positively associated with medical specialists’ motivation for work and for lifelong learning.